ESTIMATES FOR THE SECOND HANKEL–CLIFFORD TRANSFORM AND TITCHMARSH EQUIVALENCE THEOREM - S. S. Volosivets (Проблемы анализа)
We obtain estimates of integrals containing the second Hankel–Clifford transforms of functions from Sobolev-Hankel– Clifford spaces. As a corollary, we obtain a new variant of Titchmarsh equivalence theorem for the second Hankel–Clifford transform.